Translating Classical Chinese Poetry into Rhymed English: A Linguistic-Aesthetic View - Kwong, Charles (TTR)

(untitled) (Association canadienne de traductologie, 2009)
Rhyme is an important element in the fusion of sense and sound that constitutes poetry. No mere ornament in versification, rhyme performs significant artistic functions. Structurally, it unifies and distinguishes units within a poem. Semantically, it can serve to enhance or ironise sense. Emotively, it sets up pleasing resonances that deepen artistic appeal. And prosodically, rhyme can be seen as the keynote in a melody: rhyme is a modulator of pace and rhythm, while rhyme change can mark a turn of rhythm and sense in a long poem. Different languages have different combinations of linguistic resources for versification. This essay will revisit the debate on the use of rhymed English to translate classical Chinese poetry, moving beyond the general observations and experiential insights currently available to present concrete evidence on the rhyming resources and practices of English and Chinese. These comparative observations should shed new light on the linguistic and aesthetic issues involved in using rhymed English to translate classical Chinese poetry.